Preparation method of boron nitride nanosheet with large aspect ratio

Through the plasma spray gun heating spraying and ultrasonic dispersion methods, the problems of low efficiency and difficulty in preparing two-dimensional nanosheets in the prior art are solved, and the high efficiency of preparation of boron nitride nanosheets with large aspect ratios is achieved, and excellent thermal conductivity is achieved. Rate and electrical insulation properties are suitable for the preparation of dielectric capacitors.

CN119409145AActive Publication Date: 2025-02-11SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411360401.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-11
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The prior art has problems such as low efficiency, difficulty in controlling and low yield when preparing two-dimensional nanosheets of high quality, high purity, high performance and high yield, especially when using liquid phase ultrasonic peeling method and ion insertion peeling method. The solvent is costly, toxic, and the preparation process is complicated.

Method used

The boron nitride powder is heated and sprayed out by a plasma spray gun. The boron nitride is thermally expanded by high-temperature plasma jet, which weakens the van der Waals force between layers. Then it is cooled in the coolant and ultrasonic dispersed, and the precipitation is removed by centrifugation, and filtration is obtained to obtain a large aspect ratio. boron nitride nanosheets.

Benefits of technology

Achieving efficient and controllable preparation of large aspect ratio BNNSs from large-sized hexagonal boron nitride, providing a material suitable for the preparation of dielectric capacitors with ultra-high thermal conductivity, high temperature stability and excellent electrical insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409145A_ABST
    Figure CN119409145A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a boron nitride nanosheet with a large aspect ratio, and belongs to the technical field of nano material preparation. The preparation method of the boron nitride nanosheet with the large aspect ratio comprises the following steps: heating and spraying boron nitride powder by using a plasma spray gun to obtain expanded boron nitride, cooling the expanded boron nitride in a cooling liquid to obtain a precursor solution, carrying out ultrasonic treatment and centrifugation to obtain a supernatant, and filtering the supernatant to obtain the boron nitride nanosheet with the large aspect ratio. The invention develops a method for stripping boron nitride by using a plasma spray gun, which is simple, efficient and easy to operate and control. BNNSs with a large aspect ratio can be efficiently and controllably prepared from large-size hexagonal boron nitride, so that a material which is suitable for preparing a dielectric capacitor and has excellent performances such as a large aspect ratio, ultrahigh heat conductivity and high-temperature stability is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a method for preparing a boron nitride nano sheet with a large aspect ratio. Background Art

[0002] With the continuous advancement of power electronics technology, 5G technology is increasingly used in communications and other fields. At the same time, microelectronic devices are developing towards lighter and smaller sizes. This trend places higher requirements on the electrical and thermal conductivity of electronic components and energy storage materials. Among the many potential material options, two-dimensional materials have attracted much attention and become a hot topic of research due to their unique electrical, thermal, physical and chemical properties. The utilization of two-dimensional (2D) materials has become popular in several disciplines due to their special thermal, electrical and mechanical properties. Compared with zero-dimensional (0D) and one-dimensional (1D) fillers, two-dimensional fillers are more effective in improving the dielectric and energy storage properties of polymer-based composites. Two-dimensional materials with high aspect ratios have a significant impact and important role in the field of dielectric energy storage, which is mainly reflected in the following aspects: (1) Promoting charge injection and inhibiting the growth of electrical trees: Two-dimensional materials with high aspect ratios can inhibit the growth of electrical trees through the interface barrier effect, thereby enhancing the breakdown resistance of dielectric materials; (2) Improving energy storage density: Due to their unique structural characteristics, two-dimensional materials with high aspect ratios can effectively improve the energy storage density of dielectric composites by reducing filler agglomeration and hindering the formation of conductive paths. The introduction of these materials can increase the dielectric constant of the material, thereby generating stronger polarization under the action of the electric field and storing more energy. However, how to prepare high-quality, high-purity, high-performance, and high-yield two-dimensional nanosheets is a technical problem that needs to be solved urgently.

[0003] The current methods for preparing two-dimensional layered materials such as boron nitride nanosheets (BNNSs) mainly include mechanical exfoliation and chemical exfoliation. Among the mechanical exfoliation methods, although the mechanical ball milling method is easy to operate and has low requirements for environmental conditions, this method has some limitations, such as difficulty in precise control, insufficient selectivity, and low crystallinity of the prepared BNNSs. The chemical exfoliation method includes two technologies: liquid phase ultrasonic exfoliation and ion insertion exfoliation. Although the liquid phase ultrasonic exfoliation method is effective, the solvents used are not only expensive but also may be toxic; in addition, the dispersibility of BNNSs in the solvent is poor, which may cause BNNSs to re-aggregate during the solvent removal process, thereby reducing the yield of the final product. The ion insertion exfoliation method has strict requirements on environmental conditions during the ion insertion stage, which undoubtedly increases the complexity of the preparation process; in the process of removing the intercalated material, BNNSs may also re-aggregate, further affecting the yield. In order to improve efficiency and quality, the preparation process urgently needs further optimization and improvement. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing boron nitride nanosheets with a large aspect ratio to solve the above-mentioned problems in the background technology. The present invention develops a simple, efficient, easy-to-operate and controllable method for exfoliating boron nitride using a plasma spray gun. It can efficiently and controllably prepare BNNSs with a large aspect ratio from large-sized hexagonal boron nitride, thereby providing a material suitable for preparing dielectric capacitors with excellent properties such as a large aspect ratio, ultra-high thermal conductivity, and high-temperature stability.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing boron nitride nanosheets with a large aspect ratio, comprising the following steps:

[0007] Boron nitride powder is heated and sprayed using a plasma spray gun to obtain expanded boron nitride, which is placed in a coolant for cooling to obtain a precursor solution, subjected to ultrasound, centrifuged to obtain a supernatant, and filtered to obtain the boron nitride nanosheet with a large aspect ratio.

[0008] Preferably, the boron nitride powder is added to the plasma spray gun by using a separate nozzle for internal delivery. The separate nozzle can prevent the airflow for powder delivery from interfering with the arc plasma process, and the powder beam does not flush the anode.

[0009] Preferably, the coolant is isopropanol and water in a mass ratio of 4-5:5-6, more preferably 4:6.

[0010] Preferably, the boron nitride powder is hexagonal boron nitride powder (h-BN for short) with an average size of 18-22 μm.

[0011] Preferably, the cooling comprises the following steps: spraying the expanded boron nitride sprayed from a plasma spray gun directly into a cooling liquid, the temperature of the cooling liquid being 0-5°C.

[0012] Preferably, the distance between the nozzle of the plasma spray gun and the coolant is 1.5-2.5 m, more preferably 2.2 m.

[0013] Preferably, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 90-180SLPM, plasma gas N2 flow rate is 30-80SLPM, plasma gas H2 flow rate is 10-50SLPM, boron nitride powder feeding rate is 15-30g / min, powder carrier gas Ar flow rate is 9-30SLPM, and spraying power is 50-100kW.

[0014] More preferably, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 90-176SLPM, plasma gas N2 flow rate is 50-60SLPM, plasma gas H2 flow rate is 20-25SLPM, boron nitride powder feeding rate is 17-30g / min, powder carrier gas Ar flow rate is 9-20SLPM, and spraying power is 80-95kW.

[0015] Preferably, the power of the ultrasound is 25-30 kHz, and the time is 30-120 min.

[0016] More preferably, the power of the ultrasound is 25-30 kHz, and the time is 40-50 min.

[0017] Preferably, the centrifuge speed is 1500-3000 rpm and the time is 5-30 min.

[0018] More preferably, the centrifuge speed is 1500-2000 rpm and the time is 8-10 min.

[0019] Preferably, the filtering is performed through gauze with a pore size of 4-5 μm.

[0020] More preferably, the filtering is performed through gauze with a pore size of 4 μm.

[0021] Preferably, the filtration further comprises a drying step, wherein the drying temperature is 70-80°C and the drying time is 12-24 hours. More preferably, the drying temperature is 80°C and the drying time is 24 hours.

[0022] The second technical solution of the present invention is to provide a boron nitride nanosheet with a large aspect ratio obtained according to the above preparation method.

[0023] The third technical solution of the present invention is to provide an application of the above-mentioned large aspect ratio boron nitride nanosheets in the field of dielectric energy storage.

[0024] The technical principles of the present invention are as follows:

[0025] In the heating and ejecting stage, the present invention controls the temperature range of the plasma spray gun by adjusting the power, airflow ratio and flow rate of the plasma spray gun, and the boron nitride powder undergoes interlayer expansion under the action of high temperature and high-speed plasma impact to obtain expanded boron nitride. The nozzle of the spray gun is aimed at an ice water bath, and the high-temperature expanded boron nitride is directly sprayed into the ice water to achieve rapid cooling, and after cooling to room temperature, ultrasonic dispersion is performed to obtain a BNNSs suspension.

[0026] The present invention can utilize a high-temperature and high-speed plasma jet formed by a plasma spray gun to heat hexagonal boron nitride, causing the boron nitride to undergo thermal expansion, thereby weakening the van der Waals force between the boron nitride layers, and finally exfoliating the boron nitride through ultrasonic aqueous phase, thereby preparing BNNSs with a large aspect ratio. By adjusting the temperature and powder feeding rate, boron nitride nanosheets with different aspect ratios can be obtained. At a powder feeding rate of 28 g / min at 2100° C. to 2450° C., boron nitride nanosheets with an average aspect ratio of 2302 can be obtained. At a powder feeding rate of 30 g / min at 2450° C. to 2650° C., boron nitride nanosheets with an average aspect ratio of 2480 can be obtained. At a powder feeding rate of 15 g / min at 1534° C. to 1692° C., boron nitride nanosheets with an average aspect ratio of 1521 can be obtained. At 1692℃~1837℃, a powder feeding rate of 17g / min can obtain boron nitride nanosheets with an average aspect ratio of 1730. At 1837℃~1950℃, a powder feeding rate of 20g / min can obtain boron nitride nanosheets with an average aspect ratio of 1840. At 1950℃~2100℃, a powder feeding rate of 25g / min can obtain boron nitride nanosheets with an average aspect ratio of 2020.

[0027] The beneficial technical effects of the present invention are as follows:

[0028] The present invention has developed a simple, efficient, easy-to-operate and controllable method for exfoliating boron nitride using a plasma spray gun. It can efficiently and controllably prepare BNNSs with a large aspect ratio from large-sized hexagonal boron nitride, thereby providing a material suitable for preparing dielectric capacitors with excellent properties such as a large aspect ratio, ultra-high thermal conductivity, and high-temperature stability. In addition, the boron nitride nanosheets prepared by the present invention also have excellent electrical insulation properties, and the high aspect ratio means that it has a larger surface area per unit volume, which enhances its application potential in catalysis, adsorption, and sensors.

[0029] The method comprises the following steps: firstly heating hexagonal boron nitride with a supersonic plasma spray gun, directly spraying the heated hexagonal boron nitride into an ice water bath, then ultrasonically dispersing and centrifuging to remove the precipitate, filtering the supernatant, and finally drying to obtain the target product. The boron nitride nanosheets prepared by the method of the present invention are uniform in size and thickness, have a large aspect ratio, and are ahead of similar products in the prior art. In addition, the prepared boron nitride nanosheets also have excellent dielectric properties and thermal conductivity, and can be applied to high energy storage and wide temperature frequency dielectric capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 Schematic diagram of the preparation process of Examples 1-6.

[0032] Figure 2 The atomic force microscope image (a), height image (b) and lateral dimension image (c) of the product of Example 1.

[0033] Figure 3 This is a statistical distribution diagram of the lateral size and thickness data of the product of Example 1.

[0034] Figure 4 This is a physical picture of the supernatant of boron nitride nanosheets in Example 1.

[0035] Figure 5 Schematic diagram of the experimental equipment for Examples 1-6.

[0036] Figure 6 Statistical graphs of thermal conductivity of boron nitride nanosheets with different aspect ratios in Examples 1-6. DETAILED DESCRIPTION

[0037] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0038] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0041] The layered boron nitride powder used in the following embodiments and comparative examples of the present invention is a hexagonal boron nitride powder (product name: BN-HS) with a lateral average size of 20 μm, purchased from Dandong Chemical Research Institute Co., Ltd. The isopropanol used was purchased from Shanghai Titan Technology Co., Ltd. (Adamas). The atomic force microscope (AFM) image was measured by an atomic force microscope (Park-XE7).

[0042] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0043] Figure 1 Schematic diagram of the preparation process of Examples 1-6.

[0044] Example 1

[0045] A method for preparing boron nitride nanosheets:

[0046] Mix 80mL of isopropanol and 120mL of deionized water, adjust the temperature of the solution system to 4°C, obtain a coolant, and place it 2.2m below the plasma spray gun for use; use the plasma spray gun to heat and spray the boron nitride powder, and spray the expanded boron nitride directly into the coolant to obtain a precursor solution; wherein, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 140SLPM, plasma gas N2 flow rate is 55SLPM, plasma gas H2 flow rate is 24SLPM, powder carrier gas Ar flow rate is 15SLPM, powder feeding rate is 25g / min, and spraying power is 90kW; under this parameter, the temperature of the particles is between 1950°C and 2100°C, and the aspect ratio of the boron nitride nanosheets can reach 2020.

[0047] The precursor solution was ultrasonically dispersed at 30 kHz for 40 minutes to obtain a boron nitride nanosheet suspension, and then centrifuged at 2000 rpm for 10 minutes to obtain a boron nitride nanosheet supernatant.

[0048] The obtained boron nitride nanosheet supernatant was filtered through gauze with a pore size of 4 μm, and the filtered product was dried at 80° C. for 24 hours to obtain boron nitride nanosheets.

[0049] Figure 2 The atomic force microscope image (a), height image (b) and lateral dimension image (c) of the product of Example 1.

[0050] Depend on Figure 2 As can be seen from (a), the present invention successfully prepared BNNSs with a large aspect ratio.

[0051] According to the method of Example 1, 25 groups of boron nitride nanosheets were prepared repeatedly, and the lateral dimensions and thickness data of the products were statistically analyzed. Figure 3shown.

[0052] Figure 3 This is a statistical distribution diagram of the lateral size and thickness data of the product of Example 1.

[0053] Figure 4 This is a physical picture of the supernatant of boron nitride nanosheets in Example 1.

[0054] Example 2

[0055] A method for preparing boron nitride nanosheets:

[0056] Mix 80mL of isopropanol and 120mL of deionized water, adjust the temperature of the solution system to 4°C, obtain a coolant, and place it 2.2m below the plasma spray gun for use; use the plasma spray gun to heat and spray the boron nitride powder, and spray the expanded boron nitride directly into the coolant to obtain a precursor solution; wherein, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 102SLPM, plasma gas N2 flow rate is 50SLPM, plasma gas H2 flow rate is 35SLPM, powder carrier gas Ar flow rate is 17SLPM, powder feeding rate is 28g / min, and spraying power is 92kW; under this parameter, the temperature of the particles is between 2100°C and 2450°C, and the aspect ratio of the boron nitride nanosheets can reach 2302.

[0057] The precursor solution was ultrasonically dispersed at 30 kHz for 40 minutes to obtain a boron nitride nanosheet suspension, and then centrifuged at 2000 rpm for 10 minutes to obtain a boron nitride nanosheet supernatant.

[0058] The obtained boron nitride nanosheet supernatant was filtered through gauze with a pore size of 4 μm, and the filtered product was dried at 80° C. for 24 hours to obtain boron nitride nanosheets.

[0059] Example 3

[0060] A method for preparing boron nitride nanosheets:

[0061] Mix 80mL of isopropanol and 120mL of deionized water, adjust the temperature of the solution system to 4°C, obtain a coolant, and place it 2.2m below the plasma spray gun for standby use; use the plasma spray gun to heat and spray the boron nitride powder, and spray the expanded boron nitride directly into the coolant to obtain a precursor solution; wherein, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 90SLPM, plasma gas N2 flow rate is 48SLPM, plasma gas H2 flow rate is 49SLPM, powder carrier gas Ar flow rate is 20SLPM, powder feeding rate is 30g / min, and spraying power is 95kW; under this parameter, the temperature of the particles is between 2450°C and 2650°C, and the aspect ratio of the boron nitride nanosheets can reach 2480.

[0062] The precursor solution was ultrasonically dispersed at 30 kHz for 40 minutes to obtain a boron nitride nanosheet suspension, and then centrifuged at 2000 rpm for 10 minutes to obtain a boron nitride nanosheet supernatant.

[0063] The obtained boron nitride nanosheet supernatant was filtered through gauze with a pore size of 4 μm, and the filtered product was dried at 80° C. for 24 hours to obtain boron nitride nanosheets.

[0064] Example 4

[0065] A method for preparing boron nitride nanosheets:

[0066] Mix 80mL of isopropanol and 120mL of deionized water, adjust the temperature of the solution system to 4°C, obtain a coolant, and place it 2.2m below the plasma spray gun for standby use; use the plasma spray gun to heat and spray the boron nitride powder, and spray the expanded boron nitride directly into the coolant to obtain a precursor solution; wherein, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 176SLPM, plasma gas N2 flow rate is 63SLPM, plasma gas H2 flow rate is 17SLPM, powder carrier gas Ar flow rate is 9SLPM, powder feeding rate is 15g / min, and spraying power is 87kW; under this parameter, the temperature of the particles is between 1534°C and 1692°C, and the aspect ratio of the boron nitride nanosheets can reach 1521.

[0067] The precursor solution was ultrasonically dispersed at 30 kHz for 40 minutes to obtain a boron nitride nanosheet suspension, and then centrifuged at 2000 rpm for 10 minutes to obtain a boron nitride nanosheet supernatant.

[0068] The obtained boron nitride nanosheet supernatant was filtered through gauze with a pore size of 4 μm, and the filtered product was dried at 80° C. for 24 hours to obtain boron nitride nanosheets.

[0069] Example 5

[0070] A method for preparing boron nitride nanosheets:

[0071] Mix 80mL of isopropanol and 120mL of deionized water, adjust the temperature of the solution system to 4°C, obtain a coolant, and place it 2.2m below the plasma spray gun for use; use the plasma spray gun to heat and spray the boron nitride powder, and spray the expanded boron nitride directly into the coolant to obtain a precursor solution; wherein, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 163SLPM, plasma gas N2 flow rate is 60SLPM, plasma gas H2 flow rate is 19SLPM, powder carrier gas Ar flow rate is 10SLPM, powder feeding rate is 17g / min, and spraying power is 87kW; under this parameter, the temperature of the particles is between 1692°C and 1837°C, and the aspect ratio of the boron nitride nanosheets can reach 1730.

[0072] The precursor solution was ultrasonically dispersed at 30 kHz for 40 minutes to obtain a boron nitride nanosheet suspension, and then centrifuged at 2000 rpm for 10 minutes to obtain a boron nitride nanosheet supernatant.

[0073] The obtained boron nitride nanosheet supernatant was filtered through gauze with a pore size of 4 μm, and the filtered product was dried at 80° C. for 24 hours to obtain boron nitride nanosheets.

[0074] Example 6

[0075] A method for preparing boron nitride nanosheets:

[0076] Mix 80 mL of isopropanol and 120 mL of deionized water, adjust the temperature of the solution system to 4°C, obtain a coolant, and place it 2.2 m below the plasma spray gun for use; use the plasma spray gun to heat and spray the boron nitride powder, and spray the expanded boron nitride directly into the coolant to obtain a precursor solution; wherein, the parameters of the plasma spray gun are: plasma gas Ar flow rate is 151 SLPM, plasma gas N2 flow rate is 57 SLPM, plasma gas H2 flow rate is 21 SLPM, powder carrier gas Ar flow rate is 13 SLPM, powder feeding rate is 20 g / min, and spraying power is 89 kW; under this parameter, the temperature of the particles is between 1837°C and 1950°C, and the aspect ratio of the boron nitride nanosheets can reach 1840.

[0077] The precursor solution was ultrasonically dispersed at 30 kHz for 40 minutes to obtain a boron nitride nanosheet suspension, and then centrifuged at 2000 rpm for 10 minutes to obtain a boron nitride nanosheet supernatant.

[0078] The obtained boron nitride nanosheet supernatant was filtered through gauze with a pore size of 4 μm, and the filtered product was dried at 80° C. for 24 hours to obtain boron nitride nanosheets.

[0079] Figure 5 Schematic diagram of the experimental equipment for Examples 1-6.

[0080] The thermal conductivity of the products of Examples 1-6 was measured, and the test results were as follows: Figure 6 shown.

[0081] Figure 6 Statistical graphs of thermal conductivity of boron nitride nanosheets with different aspect ratios in Examples 1-6.

[0082] Comparative Example 1 (Gas Stripping Method)

[0083] A method for preparing two-dimensional hexagonal boron nitride nanosheets by gasification of liquid nitrogen:

[0084] (1) Weigh 1 g of commercial grade hexagonal boron nitride (h-BN, average size of about 5 μm) and place it in an alumina crucible, then transfer it to a high-temperature furnace, heat it to 600°C in an air atmosphere, and maintain it at this temperature for 30 minutes.

[0085] (2) The heated hexagonal boron nitride was quickly taken out and quickly transferred to a Dewar flask (-196°C) filled with liquid nitrogen, with the volume ratio of liquid nitrogen to h-BN being 1:50, until the liquid nitrogen was completely vaporized;

[0086] (3) The h-BN in the Dewar flask was transferred to a high temperature furnace and heated to 600 °C for 30 minutes;

[0087] (4) Repeat steps (2) and (3) 20 times to obtain boron nitride nanosheets.

[0088] It has been determined that the radial size of this product is 50-500nm, the number of layers is less than 10, and the thickness is <4nm.

[0089] Comparative Example 2 (Chemical Stripping Method)

[0090] A method for preparing boron nitride nanosheets:

[0091] 1 g of hexagonal boron nitride powder was mixed with 100 mL of sulfuric acid and stirred evenly, and then 0.5 g of potassium permanganate was added and stirred to prepare a mixture; the mixture was placed in an ice bath and stirred for 12 hours; then the remaining potassium permanganate was removed by dripping hydrogen peroxide; finally, the reaction product was washed with water to a pH value of 6-8, and then dissolved in anhydrous ethanol for separation, and the unpeeled boron nitride powder was removed to obtain boron nitride nanosheets.

[0092] Comparative Example 3 (Liquid Phase Ultrasonic Stripping Method)

[0093] A method for preparing boron nitride nanosheets:

[0094] Take 0.3g of hexagonal boron nitride and add it to a 300mL conical flask, then add 100mL of thionyl chloride, seal the conical flask mouth, and then place it in an ultrasonic cleaner, ultrasonicate it at a power of 210W for 5h, and then let it stand for 24h. Take out the upper milky white dispersion by careful pouring and collect it. Recover the thionyl chloride in the upper dispersion by rotary evaporation, and then place the obtained boron nitride nanosheets in a vacuum drying oven at 70°C for 24h to obtain pure boron nitride nanosheets, weighing 60mg, with a yield of 20%.

[0095] Comparative Example 4 (Mechanical Ball Milling)

[0096] A method for preparing boron nitride nanosheets:

[0097] 1) Weigh 0.25 g of hexagonal boron nitride raw material and 1.25 g of tannic acid respectively and put them into a ball milling jar, and mill them on a planetary ball mill at room temperature. The medium ball is a stainless steel ball, the ball-to-material mass ratio is 60:1, the rotation speed is 300 rpm, and the ball milling time is 20 h.

[0098] 2) The ball-milled product obtained in step 1) is fully washed with deionized water and ethanol, and then placed in a forced air drying oven to dry to obtain a light yellow powder.

[0099] 3) The light yellow powder obtained in step 2) is dispersed in isopropanol, ultrasonicated for 30 minutes, centrifuged at 2000 rpm for 30 minutes, and the supernatant is collected to obtain boron nitride nanosheets.

[0100] Comparative Example 5 (Ion Insertion Stripping Method)

[0101] A method for preparing boron nitride nanosheets:

[0102] (1) Prepare a mixed solution of 60 mL of deionized water and 40 mL of isopropanol as a dispersant; (2) Add 1 g of hexagonal boron nitride powder to the mixed solution obtained in step (1), and stir thoroughly to make the boron nitride dispersed evenly; (3) Place the dispersion obtained in step (2) in an ultrasonic cleaning machine for ultrasonic treatment for 6 hours; (4) Pour the dispersion obtained in step (3) into a hydrothermal reactor and perform a high-temperature hydrothermal reaction at 180°C; (5) Perform the same centrifugal treatment on the dispersion obtained in step (4) 3 times, with a centrifugal speed of 1000 rpm and a centrifugal time of 5 minutes. (6) Take the supernatant of step (5) and vacuum filter it 3 times with a large amount of deionized water to remove salt impurities; (7) After the product obtained in step (6) is vacuum dried at 60°C for 12 hours, boron nitride nanosheets are obtained.

[0103] The aspect ratio data of Example 1 and Comparative Examples 1-5 are shown in Table 1 (the average aspect ratio value is the average value taken after repeating the relevant preparation method 3 times).

[0104] Table 1

[0105]

[0106] As can be seen from Table 1, Example 1 has a larger aspect ratio than Comparative Examples 1-5, which helps to reduce filler agglomeration and hinder the formation of conductive paths.

[0107] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a boron nitride nanosheet with a large aspect ratio, characterized in that: The following steps are involved: Boron nitride powder is heated and sprayed using a plasma spray gun to obtain expanded boron nitride, which is placed in a coolant for cooling to obtain a precursor solution, subjected to ultrasound, centrifuged to obtain a supernatant, and filtered to obtain the boron nitride nanosheet with a large aspect ratio.

2. The preparation method according to claim 1, characterized in that: The boron nitride powder is hexagonal boron nitride powder with an average size of 18-22 μm.

3. The preparation method according to claim 1, characterized in that: The cooling comprises the following steps: the expanded boron nitride sprayed from a plasma spray gun is directly sprayed into a cooling liquid, the temperature of the cooling liquid being 0-5°C.

4. The preparation method according to claim 1, characterized in that: The parameters of the plasma spray gun are: plasma gas Ar flow rate is 90-180SLPM, plasma gas N2 flow rate is 30-80SLPM, plasma gas H2 flow rate is 10-50SLPM, boron nitride powder feeding rate is 15-30g / min, powder carrier gas Ar flow rate is 9-30SLPM, and spraying power is 50-100kW.

5. The preparation method according to claim 1, characterized in that: The power of the ultrasound is 25-30 kHz, and the time is 30-120 min.

6. The preparation method according to claim 1, characterized in that: The centrifuge speed is 1500-3000 rpm and the time is 5-30 min.

7. The preparation method according to claim 1, characterized in that: The filtration is performed through gauze with a pore size of 4-5 μm.

8. A boron nitride nanosheet with a large aspect ratio obtained according to the preparation method according to any one of claims 1 to 7.

9. Use of the large aspect ratio boron nitride nanosheets according to claim 8 in the field of dielectric energy storage.

Citation Information

Patent Citations

  • Method for preparing boron nitride nanosheet by using eutectic salt to strip boron nitride powder at high temperature

    CN105523528A

  • Preparation method of high-yield and large-size boron nitride nanosheet

    CN110668408A

  • Hexagonal boron nitride stripping method and device through arc plasma pretreatment

    CN111606312A

  • Method and device for preparing boron nitride nanosheet

    CN115417386A

  • Direct-current arc plasma device with arc root air inflow

    CN216217685U